Damage identification of structures using experimental modal analysis and continuous wavelet transform - A. Gholizad; H. Safari (Numerical Methods in Civil Engineering)
Abstract:Modal analysis is a powerful technique for understanding the behavior and performance of structures. Modal analysis can be conducted via artificial excitation, e.g. shaker or instrument hammer excitation. Input force and output responses are measured. That is normally referred to as experimental modal analysis (EMA). EMA consists of three steps: data acquisition, system identification and modal parameter estimation. EMA, which is also known as frequency response function (FRF) testing, has been widely preferred for the modal parameter estimation of structures. The main objective of this paper is to determine the locations of damages by applying the wavelet transform to the measured mode shapes. The mode shapes are obtained from EMA by applying FRF of structure as the input data. In the present work, a two-stage method of determining the location of multiple structural damages on space structures is proposed. Firstly, EMA is applied to estimate the first mode shape of space structure by applying FRF as input data. In the second stage the mechanism of using 2D- CWT is applied by exploiting the concept of simulating the mode shape of space structure to a 2D spatially distributed signal for damage localization of space structure. Multiplicities of structural elements and joints are the main challenges related to damage detection of space structure. The validation of EMA is performed with modal assurance criterion (MAC). Seven numerical examples are conducted on two double layer diamatic domes with different sizes to assess the effectiveness of the proposed 2D-CWT method. The results demonstrate the reliability and applicability of the introduced method.